Is There a Career and Technical Education Coursetaking Pipeline between High School and College?. Issue 3 (March 2019) - Plasman, Jay Stratte; Gottfried, Michael A.; Sublett, Cameron
Background: Previous studies have explored the relationship between career and technical education (CTE) on numerous secondary and college outcomes. However, a key oversight in the literature is the examination of the CTE coursetaking pipeline as it makes a direct connection between high school and college. Research Questions: We asked the following research questions to address the gap in CTE literature around secondary to postsecondary pipelines: (1) Does taking CTE courses in high school predict taking CTE courses in college? (2) Does this relationship differ between students who attend 2- and 4-year colleges? (3) Does the relationship differ by different areas of CTE? Research Design: To respond to these questions, we used the Education Longitudinal Study of 2002 (ELS:2002), a nationally representative dataset. We employed basic logistic regression, school fixed effects, and instrumental variable estimations to reduce biases in our estimations in the relationship between high school and college CTE coursetaking. Results: We found that CTE coursetaking in high school linked to overall CTE coursetaking across all years of college. When examining 2- and 4-year college coursetaking independently, only the relationship between high school and 4-year college CTE coursetaking was significant. We also found that there existed differential linking based on type of institution in which the courses were completed and area of CTE—specifically, applied STEM, business, trade and industry, and health. Conclusions: A first implication from these findings is that CTE in high school, which is itself funded through the current iteration of the Perkins legislation, appears to be having a noticeable link to CTE participation in college. From the second research question, there could very well be a strong connection between high school CTE and 2-year enrollment that is not reflected in first year CTE coursetaking at the 2-year level. Finally, the implications from the third research question speak to the need to focus on CTE as a group of individual categories as opposed to a single overarching group.